Simple beginnings : soldering jewelry : a step-be-step guide to creating your own necklaces, bracelets, rings & more - Wilson, Suzann Sladcik (Design Originals, an imprint of Fox Chapel Publishing, 2012)
"Soldering is a popular jewelry-making technique that can produce beautiful results, but if you've never had the chance to pick up a soldering iron, the process can seem daunting. Where can you find the tools you will need? What do you do with them once you have them? And what materials should you work with? In Simple Beginnings: Soldering Jewelry, renowned artist Suzann Sladcik Wilson will put all these questions to rest. Wilson will take you to the very beginning of the soldering process and teach you about the tools you will need and the materials you should buy. Then, she will take you step-by-step through the basic soldering techniques you will need to know to create your own woks of art using copper foil. Projects for beginner, intermediate, and advanced craft enthusiasts are included, ensuring that you'll always have something new to inspire and create as your skills increase. Use this book to make pendants, bracelets, earrings, frames, and more, all in your own unique, creative style. Get started today!"--